Синтез технологій платформ хмарних обчислень - Лозінський, А.П. (Control systems & computers, 2019)
Розглянуто історію формування ідеї реалізації синтезу єдиного середовища хмарних обчислень з окремих напрямків інформаційних технологій. Запропоновано реструктурований варіант оригінальної моделі багаторівневої архітектури платформи хмарних обчислень. Представлено застосування моделі у формалізації процесу оптимізації структури перерозподілу ресурсів методом комбінаторної оптимізації. Розглянуто можливість залучення хмарних обчислень до організації наукової діяльності. Цель статьи: представить процесс синтеза технологий в рамках идеи облачных вычислений; рассмотреть многоуровневый механизм абстрагирования в реализации ключевых свойств облачных вычислений на основе понятий "услуга" и "сервис-ориентированная архитектура"; представить разработанную автором модель многоуровневой архитектуры платформы облачных вычислений с описанием взаимодействия между уровнями; рассмотреть применение комбинаторной оптимизации в процессе перераспределения ресурсов платформ облачных вычислений между рабочими нагрузками; определить перспективы применения локальной платформы облачных вычислений в организации научной деятельности. Результаты. Предложен реструктурированный вариант оригинальной модели многоуровневой архитектуры платформы облачных вычислений. Представлено применения модели в формализации процессов оптимизации структуры перераспределения ресурсов методами комбинаторной оптимизации. Рассмотрена возможность привлечения облачных вычислений в организации научной деятельности. Purpose. The purpose of this article is: 1) to present the process of synthesis of technologies in the framework of the idea of cloud computing; 2) consider a multi-level mechanism of abstraction in the implementation of the key properties of cloud computing based on the concepts of "service" and "service-oriented architecture"; 3) to present a model of a multilevel architecture of a cloud computing platform developed by the author with a description of the interaction between the levels; 4) consider the use of combinatorial optimization in the process of redistributing the resources of cloud computing platforms between workloads; 5) determine the prospects for the use of the local cloud computing platform in the organization of scientific activity. Methods. The methods of abstraction, modeling, leveling, combinatorial optimization are used. Results. A restructured version of the original model of multi-level architecture of the cloud computing platform is proposed. The application of the model in formalizing the processes of optimizing the structure of the redistribution of resources by combinatorial optimization methods is presented. The possibility of attracting cloud computing in the organization of scientific activity is considered.